Pengembangan Simpul Wisata Potensial Berbasis Triangulasi Analysis di Kecamatan Tosari Kabupaten Pasuruan - Khusnul Khotimah (Syntax Idea)
Tosari District as the gateway to the national tourism area of Mount Bromo does not yet have the right infrastructure node to be used as a gathering point for tourists. This condition is indicated by the high movement of tourists to the Bromo area but not matched by the provision of adequate parking facilities to switch modes; many tourists' vehicles are parked along the road because there are no parking spaces, especially during holidays; There has been no determination of the exact nodal point as the estuary of tourist movements in Tosari District. This research aims to analyze the characteristics of tourist movements and surrounding communities as well as traffic performance in Tosari District; analyze the selection of alternative locations for the Type C Terminal in Tosari District that is appropriate and in accordance with the pattern of people's transport movements; determine the appropriate location for the construction of the Type C Terminal in Tosari District. Results of the analysis through the triangulation analysis method, namely a combination of analysis by considering the distribution of movement factors, considering the geographical conditions in Tosari District which is an area that has terrain in the form of mountains and slopes, as well as the results of interviews with experts consisting of Village Officials, Perhutani, and the District Transportation Office Pasuruan. Based on the results of a survey of generation and attraction in Tosari District, the largest generation potential was found in the TNBTS zone of 1,022 people/day on holidays and 498 people/day on weekdays. Meanwhile, the biggest attraction in the Tosari Village zone is 548 people/day on holidays and 208 people/day on weekdays. Based on the results of interviews and questionnaires with node users purposively, it was found that 55% chose Tosari Village as the location for the node construction because it was considered more convenient in modal shifting and affordable for private vehicles before the modal shift was carried out to Penanjakan and TNBTS. Choiceâ€ obtained 2 alternative locations namely Priority 1 Location in Banyu Petoeng Tosari Village with an assessment weight of 53.08%, and the 2nd alternative location in Tosari Rest Area Tosari Village with 23%.